Правові засади безпекової політики України в умовах євроінтеграції - Загуменна, Ю. О.; Zagumenna, Yu. O.; Юлія Загуменна (Вчені записки ТНУ імені В. І. Вернадського. Сер.: Юридичні науки. – 2023. – Т. 34 (73), № 4. - С. 8-22, 2023)
Проаналізовано міжнародно-правові документи Європейського Союзу з безпекових питань, а також визначено завдання і пріоритетні напрями діяльності Євросоюзу у згаданій сфері. З’ясовано змістовні характеристики Стратегії зовнішньої політики та політики безпеки ЄС, визначено особливості співпраці України з Європейським Союзом у безпекових питаннях, а також з’ясовано місце нашої держави у механізмі забезпечення безпеки і стабільності в Європі.

On the way to Ukraine’s European integration, security issues become more and more relevant along with traditional issues in the field of politics and economy. There are all grounds for this, namely, Russia’s full-scale armed aggression against Ukraine, the kinship of interests in the security sphere of Ukraine and the European Union, as well as the constantly growing security potential of our state, which can be effectively used in mutual interests in the post-war period. The relevance of the chosen research topic is due to the importance of the issues considered for Europe in the whole and for Ukraine as its component, on the one hand, and on the other hand, as a state, where the European Union is one of the priority directions of its foreign policy. The purpose of this article is to clarify the substantive characteristics of the EU’s Foreign and Security Policy Strategy, to determine specific features of Ukraine’s cooperation with the European Union in security issues, as well as to clarify the place of our state in the mechanism of ensuring security and stability in Europe. The legal aspects of Ukraine’s security policy in the context of European integration aspirations have been studied taking into account Russia’s open armed aggression against our country. We should note that the European Union has gained considerable experience in the field of security in the region in regard to the interaction between the member states of the Union and its central security agencies, as well as in regard to cooperation with certain non-EU countries, including Ukraine. The study of cooperation issues with the European Union in the security sector is conditioned by the Russian Federation’s unleashing a full-scale war against Ukraine, as well as by the need for our country, who claims to actively participate in addressing security challenges in Europe, to have a balanced scientific analysis of the EU Foreign and Security Policy Strategy and other security issues related to Russia’s armed aggression against Ukraine. This article is an attempt to contribute to the apprehension of new opportunities of the European Union in implementing security policy, which are important both for Ukraine and EU member states, and subsequently for the perspectives of Ukraine’s foreign policy in the European focus area.

Проанализированы международно-правовые документы Европейского Союза по вопросам безопасности, а также определены задачи и приоритетные направления деятельности Евросоюза в упомянутой сфере. Выяснены содержательные характеристики Стратегии внешней политики и политики безопасности ЕС, определены особенности сотрудничества Украины с Европейским Союзом по вопросам безопасности, а также выяснено место нашего государства в механизме обеспечения безопасности и стабильности в Европе.
Legal basis of Ukraine’s security policy in the context of European integration
Keywords: безпекова політика; security policy; политика безопасности; Європейський Союз; European Union; Европейский Союз; Україна; Ukraine; Украина; Стратегія зовнішньої політики та політики безпеки ЄС; EU Foreign and Security Policy Strategy; Стратегия внешней политики и политики безопасности ЕС; збройна агресія; armed aggression; вооруженная агрессия; євроінтеграція; European integration; евроинтеграция